TACTICAL AND STATISTICAL ANALYSIS OF GAME MODELS OF LEADING VOLLEYBALL TEAMS IN THE CONTEXT OF THE MODERN COMPETITIVE PROCESS (World Bulletin of Physical Education and Sports Science, 2025)
This study is devoted to a comprehensive tactical and statistical analysis of game models used by leading volleyball teams within the framework of the modern competitive process. Contemporary volleyball is characterized by a high level of intensification, variability of tactical decisions, and the widespread use of data-driven approaches in performance management. Under these conditions, the effectiveness of a team increasingly depends on the optimal integration of tactical structures with statistically grounded decision-making. The relevance of the research is determined by the growing role of match analytics in elite volleyball, where even minor advantages in serve efficiency, attack organization, blocking systems, or defensive transitions can have a decisive impact on match outcomes.
Keywords: Tactical analysis, statistical indicators, volleyball game models, competitive activity, team performance, match analytics.